Ship Motion Control Course Keeping and Roll Stabilisation Using Rudder and Fins - Perez, Tristan; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2005)
The impact of control system design on ship performance has been significant in different applications of ship motion control: course keeping, station keeping, roll stabilisation and vertical motion/riding control, diving, path following, etc. This monograph introduces ship motion control by studying the particular problems of control system design for course autopilots with rudder roll stabilisation and combined rudder–fin stabilisers. Ship Motion Control revisits the ingredients that make these control designs challenging and proposes a contemporary control system design approach to meet that challenge. The key ingredients for a successful ship motion control system design are: • appropriate mathematical models of the ship and the disturbances; • understanding of how performance will be assessed; • knowledge of fundamental limitations that may prevent designs from achieving the desired performance. The book is organised in four parts, the first three dealing with each of these and the fourth part addressing control system design. Specific topics covered include: • modelling and simulation of ocean waves; • ship dynamics; • models of actuators; • ship roll stabilisation devices; • ship motion performance; • analysis of fundamental limitations for stabiliser control system design; • constrained control design via optimisation; • autopilot design using optimal control; • wave filtering; • control system design for autopilots with rudder roll stabilisation; • control system design for integrated rudder-fin stabiliser. Ship Motion Control will be of interest not only to the practising marine engineer but to the academic engaged in research into this important control problem, even if new to the area. It will also be an ideal source of reference for students and tutors involved with marine and control engineering courses. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.
Ship Modelling for Control -- Environmental Disturbances -- Kinematics of Ship Motion -- Ship Kinetics -- Control Surfaces (Actuators) -- to Ship Motion Control -- to Ship Roll Stabilisation -- Ship Roll Stabilisation -- Ship Motion Performance -- Performance Limitations in Feedback Control with Application to Ship Roll Stabilisers -- Linear Performance Limitations -- Constrained Performance Limitations -- Control System Design for Autopilot with Rudder Roll Stabilisation and Fin Stabilisers -- Previous Research in Control of Rudder Roll Stabilisation and Fin Stabilisers -- Constrained Control via Optimisation -- Control System Design for Autopilots with Rudder Roll Stabilisation -- Constrained Control of Fin Stabilisers.
Keywords: Mechanical engineering; Control engineering; Engineering design; Industrial engineering; Production engineering; Ocean engineering; Mechanical Engineering; Control and Systems Theory; Engineering Design; Industrial and Production Engineering; Offshore Engineering